Pengaruh Gaya Kepemimpinan Spiritual, Lingkungan Kerja, dan Motivasi Ekstrinsik terhadap Kepuasan Kerja Karyawan Super Dazzle Gejayan Yogyakarta - Aldi Rohmadon; Prayekti Prayekti (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
The purpose of this study is to describe (1) the influence of spiritual leadership style on employee job satisfaction. (2) The influence of the work environment on employee job satisfaction. (3) The effect of extrinsic motivation on employee job satisfaction. (4) The influence of spiritual leadership style, work environment, and extrinsic motivation on employee job satisfaction.This research is a type of quantitative research, with a population of all employees of Super Dazzle Gejayan Yogyakarta. The sampling technique in this study is a non-probability sampling technique where the technique used is saturated sampling (census). The number of samples in this study were 80 employees of Super Dazzle Gejayan Yogyakarta. Data collection techniques in this study used a questionnaire. The data analysis methods used in this research are validity test, reliability test, descriptive test, classical assumption test, and multiple linear regression test. The data analysis was conducted to identify the independent variables that affect the dependent variable.The results showed that (1) spiritual leadership style had an effect on employee job satisfaction. (2) The work environment has no effect on employee job satisfaction. (3) Extrinsic motivation has an effect on employee job satisfaction. (4) Spiritual leadership style, work environment, and extrinsic motivation simultaneously affect employee job satisfaction. Keywords: Spiritual leadership style, Work environment, extrinsic motivation, job satisfaction